What law should apply then? The implications of the successful invocation of the public policy defence in EU private international law in family matters - Aquironi, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The EU legislation in the area of private international law addresses explicitly the “negative” aspect of public policy, i.e. the non-application of the otherwise applicable law on the ground that it is at variance with the fundamental values of the forum. By contrast, the legislative measures adopted so far remain silent as to the law or rules that one should apply as a result of the successful invocation of the public policy defence. The paper aims, first, to assess the approach whereby the latter issue should be decided in accordance with the private international law rules of the forum. Secondly, the paper contends that an autonomous solution to the issue of the subsidiarily applicable law should mirror the goals pursued by the EU legislator – namely autonomy, flexibility, proximity and foreseeability –, and enshrined in the already adopted instruments dealing with the conflict of laws, rather than following the more widely known and endorsed approaches either not ensuring foreseeability and legal certainty, or leading to the immediate application of the lex fori. The focus will be on conflict-of-law rules in family matters, although similar patterns can be exported to other areas of the judicial cooperation in civil and commercial matters.